Exploring Cryptocurrency: Commodity Basket-Based Stablecoin, Asia Cryptocurrency Regulatory Risk Index, and Futures Exchange (FTX) Herding Behaviour - Chin, Tze Chi (Curtin University, 2024)
Cryptocurrency is an innovative creation. In this study, a commodity basket-based stablecoin is proposed through the employment of interviews, portfolio optimisation, and wavelet analysis. An Asia Cryptocurrency Regulatory Risk Index is constructed using Latent Dirichlet Allocation (LDA), and the herding behaviour during the FTX collapse is examined. Collectively, this study explores the diverse aspects of stability and risk within the cryptocurrency market, providing valuable information for effective decision-making and risk management.